ESSAY REVIEW Disappointing “documentary” about Loch Ness Monsters (“Nessies”) (Can good documentaries be made about such subjects?) - Bauer, Henry (Journal of Scientific Exploration, 2020)
“About the show: Professor Neil Gemmell uses cutting-edge environmental DNA science to unravel the mystery of the Loch Ness monster. Neil’s high-tech monster hunt opens a new chapter in the search for Nessie as he puts the leading theories to the ultimate scientific test.” [i] This description misleads in every important respect. The mystery is not unraveled; the leading theory is not even mentioned, and Gemmell’s reason for embarking on this project — namely, to spread awareness of the potential benefits that can accrue from research on environmental DNA (eDNA) — is not well served, because there is no useful explanation of what eDNA science does, what it can and cannot accomplish, and why [ii]. That lack is all the sadder because the results in this case with respect to Nessies are not only incomplete, they are inconclusive and probably even wrong in an important respect. [i] https://www.travelchannel.com/shows/loch-ness-monster-new-evidence [ii] That eDNA work is not easy or infallible is pointed out in a comment on Roland Watson’s informative and reliable blog: “as with any tests that involve biologicals, there are error rates. And eDNA is not immune to these errors. . . . eDNA testing is also affected by seasonal changes — of how creatures operate in their environment, as well as the quality of the effluent at different times of the year, and so on. . . . [F]or eDNA testing to detect creatures properly there would have to be such testing throughout Loch Ness on a quarterly basis over probably at least two years, and probably have close to 350 to 450 sampling points — and doing this at least at five or six different consistent depths. I think that Roland correctly pointed out that nothing was taken way down deep, and there probably should have been. Also, eDNA actually lasts much, much longer in soils than in water. So taking samples off the Loch bottom might be a fruitful endeavor.” Indeed, there are several clues indicating that Nessies spend most of their time down deep, possibly in the two basins known to be deeper than 200 m (Shine & Martin 1988).